Effect of decreasing respiratory rate on the mechanical power of ventilation and lung injury biomarkers: a randomized cross-over clinical study in COVID-19 ARDS patients - L. Felipe Damiani; Roque Basoalto; Vanessa Oviedo; Leyla Alegria; Dagoberto Soto; M. Consuelo Bachmann; Yorschua Jalil; Cesar Santis; David Carpio; Rodrigo Ulloa; Daniel Valenzuela; Magdalena Vera; et al. (Intensive Care Medicine Experimental)
Abstract Background The respiratory rate (RR) is a key determinant of the mechanical power of ventilation (MP). The effect of reducing the RR on MP and its potential to mitigate ventilator-induced lung injury remains unclear. Objectives To compare invasive ventilation using a lower versus a higher RR with respect to MP and plasma biomarkers of lung injury in COVID-19 ARDS patients. Methods In a randomized cross-over clinical study in COVID-19 ARDS patients, we compared ventilation using a lower versus a higher RR in time blocks of 12 h. Patients were ventilated with tidal volumes of 6 ml/kg predicted body weight, and positive-end-expiratory pressure and fraction of inspired oxygen according to an ARDS network table. Respiratory mechanics and hemodynamics were assessed at the end of each period, and blood samples were drawn for measurements of inflammatory cytokines, epithelial and endothelial lung injury markers. In a subgroup of patients, we performed echocardiography and esophageal pressure measurements. Results We enrolled a total of 32 patients (26 males [81%], aged 52 [44–64] years). The median respiratory rate during ventilation with a lower and a higher RR was 20 [16–22] vs. 30 [26–32] breaths/min (p < 0.001), associated with a lower median minute ventilation (7.3 [6.5–8.5] vs. 11.6 [10–13] L/min [p < 0.001]) and a lower median MP (15 [11–18] vs. 25 [21–32] J/min [p < 0.001]). No differences were observed in any inflammatory (IL-6, IL-8, and TNF-R1), epithelial (s-RAGE and SP-D), endothelial (Angiopoietin-2), or pro-fibrotic activity (TGF-ß) marker between high or low RR. Cardiac function by echocardiography, and respiratory mechanics using esophageal pressure measurements were also not different. Conclusions Reducing the respiratory rate decreases mechanical power in COVID-19 ARDS patients but does not reduce plasma lung injury biomarkers levels in this cross-over study. Study registration This study is registered at clinicaltrials.gov (study identifier NCT04641897)